Management of Pseudomembranous Candidiasis on the Tongue of a Smoker Patient - Hernawati, Sri (Health Notions, 2018)
Introduction: Candidiasis is an oral opportunistic infection caused by Candida albicans (C. albicans). This fungus may cause a pathogenic condition, and is the most common fungal infection in the human oral cavity. Candida albicans causes infection more frequently compared to other types of fungus, e.g. C. tropicalis, C. krusei, C. parapsilosis, C. guilliermondi. Predisposing factors e.g. the use of dentures, xerostomia, and smoking habits are known to cause the occurrence of oral candidiasis. Objective: To determine the management of Acute Pseudomembranous Candidiasis. Case: A 52-year-old male patient visited the Oral Medicine Clinic of Dental Hospital, Dentistry Faculty, Jember University complaining about his tongue suffering from thickening, white, and feeling uncomfortable when eating. The patient claimed hurt, and tasted bitter sensation while eating. Conclusion: The patient was completely diagnosed to suffer from pseudomembranous candidiasis on his tongue. Management: The therapy provided for the patient was Nystatin oral suspension functioning as a topical antifungal medicine, Becomzet (Vitamin B complex, A, C, E, and Zinc), tongue cleaner number 1 as a tongue cleanser appliance. Keywords: Pseudomembranous candidiasis, Tongue